2020
DOI: 10.21203/rs.3.rs-34812/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GM-CSF Expression and Macrophage Polarization in Joints of Undifferentiated Arthritis Patients Evolving to Rheumatoid Arthritis or Psoriatic Arthritis

Abstract: Background and Aims: GM-CSF-dependent macrophage polarization hasbeen demonstrated in rheumatoid arthritis (RA). Our aim was to seek diagnostic/prognostic biomarkers for undifferentiated arthritis (UA) by analyzing GM-CSF expression and source, macrophage polarization and density in joints of patients with UA evolving to RA or PsA compared with established RA or PsA, respectively.Methods:Synovial tissue (ST)from patients with UA evolving to RA (UA>RA, n=8), PsA (UA>PsA, n=9), persistent UA (UA, n=16), es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The lack of DMARD treatment in the UA group might have contributed to this observation. However, we have previously shown that UA patients evolving to RA or PsA, but not UA patients remaining as UA, had a significant increase in CD163 + macrophages compared with definitive PsA or RA patients, independently of csDMARD therapy ( 21 ). Furthermore, a study in 42 patients with untreated undifferentiated inflammatory seronegative arthritis reported that 6 patients who differentiated during the follow up (2 RA, 2 PsA, and 2 pSpA) had significantly higher synovial CD68 + macrophage scores compared with patients remaining undifferentiated, in line with our results ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of DMARD treatment in the UA group might have contributed to this observation. However, we have previously shown that UA patients evolving to RA or PsA, but not UA patients remaining as UA, had a significant increase in CD163 + macrophages compared with definitive PsA or RA patients, independently of csDMARD therapy ( 21 ). Furthermore, a study in 42 patients with untreated undifferentiated inflammatory seronegative arthritis reported that 6 patients who differentiated during the follow up (2 RA, 2 PsA, and 2 pSpA) had significantly higher synovial CD68 + macrophage scores compared with patients remaining undifferentiated, in line with our results ( 22 ).…”
Section: Discussionmentioning
confidence: 99%